Perfluorinated alkyl substances in snow as an atmospheric tracer for tracking the interactions between westerly winds and the Indian Monsoon over western China. (March 2019) - Wang, Xiaoping; Chen, Mengke; Gong, Ping; Wang, Chuanfei
Abstract: Snow is an efficient scavenger for the deposition of contaminants. Atmospheric transport and snow deposition jointly control the distribution of pollutants in remote mountain/polar regions. But can the contaminants contained within snow be used to reflect the interactions of air circulation patterns? The physicochemical properties of perfluoroalkyl substances (PFASs) are unique because of their high water solubilities. Taking advantage of this, 15 surface-snow and 3 snow-pit samples were collected across a vast area of western China (spanning 20° of latitude and 25° of longitude), to investigate the concentrations, composition profiles (fingerprints), and deposition fluxes of PFASs. Both a high concentration (3974 pg/L) and deposition flux (4.0 μg/m 2 /yr) for a total of 16 PFASs were found in the snow at Yulong, the most southern sample site, possibly because of its close proximity to source regions of pollutants in South Asia and high rate of snow deposition. Perfluorobutanoic acid was the most commonly found chemical in snow, but in general the PFAS composition in the snow of western China showed large spatial differences, with long-chain (C > 10) PFASs being relatively dominant in the north and west of the region and short-chain (C < 6) PFASs in the south and east. On the basis of the different compositions of PFASs in the snow of western China and the previously reported features of pollutant sources in Europe and India, we found that PFASs in snow can be used as an atmospheric tracer for tracking the interactions between westerly winds and the Indian Monsoon. The belt along 33°N is a key location where both the Indian Monsoon and westerly winds can arrive/interact; however, the contribution of the monsoon was found to be above 70%, while that of the westerly winds can be lower than 30%. The western part of the 33°N belt was found to be more vulnerable to the Indian Monsoon, and could be grouped into the monsoon domain, while the influence of the westerly winds increased from west to east along the belt. This finding is opposite to previous results, which reported that the western part of the 33°N belt was mainly under the influence of the westerly winds, and for the first time quantifies the relative contribution of westerly winds and the Indian Monsoon to the atmospheric transport of chemicals. Graphical abstract: Unlabelled Image Highlights: Perfluorobutanoic acid is the most commonly found chemical in snow from western China. Long-chain PFASs are relatively dominant in north and short-chain PFASs in south. PFASs in snow can be used as an atmospheric tracer. The belt along 33–35°N is a key location where the Indian Monsoon interact with westerly winds.